2021
DOI: 10.1088/1361-6463/ac04e4
|View full text |Cite
|
Sign up to set email alerts
|

Review on decomposition characteristics of eco-friendly gas insulating medium for high voltage gas insulated equipment

Abstract: Sulfur hexafluoride (SF 6 ), one of the most potent greenhouse gases with a global warming potential of 23 500 and an atmospheric lifetime of 3200 years, has been widely used as an insulating gas. The search for eco-friendly gas insulating medium to replace SF 6 has been a hot topic in the power industry over the past 5 years. The performance evaluation of eco-friendly gas insulating medium concentrates on several dimensions including stability and decomposition characteristics. This review focuses on recent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 140 publications
2
23
0
Order By: Relevance
“…Apart from issues in terms of surface charge accumulation, SF 6 , which has long been used as the main component of the gas insulation, has significant impact on the global warming. Investigating future environmental-friendly insulating gas has become a hot topic [32,33]. Also, forward-looking research regarding recyclable solid insulating materials (i.e.…”
Section: Gas-insulated Equipmentmentioning
confidence: 99%
“…Apart from issues in terms of surface charge accumulation, SF 6 , which has long been used as the main component of the gas insulation, has significant impact on the global warming. Investigating future environmental-friendly insulating gas has become a hot topic [32,33]. Also, forward-looking research regarding recyclable solid insulating materials (i.e.…”
Section: Gas-insulated Equipmentmentioning
confidence: 99%
“…To replace SF 6 gas in engineering [29], the relative DS, BT, and GWP of the gas must be comprehensively considered.…”
Section: Design Range For Sf6 Potential Substitute Gas Moleculesmentioning
confidence: 99%
“…In recent years, C 4 F 7 N (perfluoroisobutyronitrile) has been recognized as a promising alternative gas due to its advanced insulation and eco-friendly performance [6,7]. It has a GWP of 2090 and an atmospheric life of 22 years.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the dielectric strength of pure C 4 F 7 N gas is twice that of SF 6 and the insulation performance of C 4 F 7 N/CO 2 with 18%-20% C 4 F 7 N is equivalent to that of SF 6 [9]. Comprehensive performance evaluations of C 4 F 7 N on insulation performance [6][7][8][9], decomposition characteristics [10,11] and material compatibility [12] have been conducted, and have demonstrated that C 4 F 7 N has the application potential for both medium-voltage and high-voltage GIE. For example, General Electric successfully developed a 245 kV current transformer and 145 kV gas-insulated switchgear with C 4 F 7 N gas as the insulation medium and put them into trial operation [13].…”
Section: Introductionmentioning
confidence: 99%